2013
DOI: 10.1002/jclp.22026
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Loss and Posttraumatic Stress and Depressive Symptoms Following Hurricane Ike

Abstract: Disasters can have wide-ranging effects on individuals and their communities. Loss of specific resources (e.g., household contents, job) following a disaster has not been well studied, despite the implications for preparedness efforts and post-disaster interventions. The present study used random-digit-dial methodology to recruit hurricane-affected adults from Galveston and Chambers, TX, counties one year after Hurricane Ike. Data from 1,249 survivors were analyzed to identify predictors of distress, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Consistent with previous studies, the univariable analyses revealed that home damage, life-threatening events, witnessing other people experiencing traumatic events, and lack of necessities were all significant correlates of PTSD (Chan & Rhodes, 2014;Paul et al, 2014;Ursano et al, 2014). Financial loss was identified as a consistent predictor of PTSD in previous literature (Galea, Tracy, Norris, & Coffey, 2008;Silvestre et al, 2014), but was not significant in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies, the univariable analyses revealed that home damage, life-threatening events, witnessing other people experiencing traumatic events, and lack of necessities were all significant correlates of PTSD (Chan & Rhodes, 2014;Paul et al, 2014;Ursano et al, 2014). Financial loss was identified as a consistent predictor of PTSD in previous literature (Galea, Tracy, Norris, & Coffey, 2008;Silvestre et al, 2014), but was not significant in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Brewin, Andrews, and Valentine (2000) argue that methodological differences between these studies renders direct comparisons between these groups difficult, with both rates of long term PTSD and identification of risk factors varying wildly. A number of factors have been identified that appear to predict a chronic course of post-traumatic stress following a traumatic event in several civilian populations including personal losses, personal exposure to the traumatic incident, personal injury, and perceived threat (Paul et al, 2014). McFarlane (1988d) found that none of these factors predicted the emergence of PTSD symptoms among a sample of firefighters 25 months after exposure to a traumatic event suggesting that the risk factors for the development of post-traumatic stress symptoms among firefighters may be unique to this population.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, having more resources can buffer against future resource loss and also facilitate future resource gain (Hobfoll, 1998) [11]. These patterns have been supported through studies showing that material resource loss predicts personal characteristic resource loss in the form of psychological distress [13,14], whereas resource gain is only critical in predicting distress in the context of loss [15]. …”
Section: Introductionmentioning
confidence: 99%